The Effectiveness of the Example Learning Method using Documentary Films on The G30S/PKI Incident to Improve Critical Thinking Skills of Students at Islamic High Schools in Tangerang Regency - Suhaeni, Een; Ribawati, Eko; Fadillah, Moh. Ali (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research aims to find out The Effectiveness of Example Learning Method through Documentary film Media Of G30S/PKI Events To Improve Critical Thinking Skills Of MA Islamiyah Tangerang Regency Students. The method used in this research is quasi eksperimen, with nonprobability sampling technique, totaling 41 people each in the experimental class and control class. The instrument used in this research is a 10 question description test. The results of hypothesis testing t test with one way anova formula, the ekerimental class obtained = 465.638 < 161 by a = 0.05 while in the control class  = 211.938 <  161 by a = 0.05 So that Ha is accepted Ho is rejected. Based on the data analysis, the example learning method is effective in improving students' critical thinking skills. This shows the effective example learning method can improve critical thinking skills. This is evidenced by looking at the results of the pretest and posttest with the average posttest score of 36 and the posttest with the average score reaching 80. It can be seen from this value that the example learning method has an effect on students' critical thinking skills in Indonesian history subjects using documentary film media.